Governance and organization of Academic Medical Centers – a comparative analysis of 11 countries. (20th October 2021) - Cardinaal, E; Dubas-Jakóbczyk, K; Behmane, D; Bryndová, L; Cascini, F; Duighuisen, H; van Ginneken, E; Waitzberg, R; Jeurissen, P
Abstract: Background: Academic Medical Centers (AMCs) are organizations that link three functions: providing highly specialized medical services, teaching activities and conducting research. The aim of the study was to provide an international comparison of the governance and organization models of AMCs. The analysis covered 10 European countries (Cyprus, Czechia, Denmark, Germany, Italy, Latvia, Netherlands, Norway, Poland, Spain) and Israel. Methods: The study has an explorative and descriptive character. The methods involved: (1) the creation of a conceptual framework; (2) the development of a dedicated questionnaire; (3) data collection and analysis. The data was collected based on purposive sampling. There were 26 respondents from 11 countries. Results: There is no standardized definition of AMCs across countries. Different types of hospital providers do link patientcare, teaching and research. Depending on the country and particular institution, the balance between these three functions, as well as the scope might vary a lot. The majority of the participating countries face either public or not-for-profit ownership for AMCs and medical faculties. However, the relationship between hospital and faculty varies substantially. Main internal governance challenges focus on lack of responsiveness to change and financial conflicts between the three core tasks. External challenges relate to financial sustainability and workforce shortages. Most respondents believe that in the nearby future the governance of AMCs will evolve to a more functionally integrated model of the three functions. Conclusions: The study fills the gap in the literature on organization and governance of European AMCs. Although, there are substantial differences in the models of governance across countries, many challenges are highly similar. This raises important questions for future research (e.g. focusing solely on one function) as well as policy (the potential for cross-national learning). Key messages: There is no standardized definition of AMCs across countries and different types of organizations are used to link the three functions of providing patientcare, teaching activities and research. Despite the organizational and legal differences, AMCs in different countries face similar challenges (nimbleness and financial conflicts between the three functions; health workforce shortages).